Optimal combination of the correction model and parameters for the precision geometric correction of UAV hyperspectral images - Tian, Wenzhong; Kan, Za; Zhao, Qingzhan; Jiang, Ping; Wang, Xuewen; Liu, Hanqing (International Journal of Agricultural and Biological Engineering, 2024)
Nowadays, with the rapid development of quantitative remote sensing represented by high-resolution UAV hyperspectral remote sensing observation technology, people have put forward higher requirements for the rapid preprocessing and geometric correction accuracy of hyperspectral images. The optimal geometric correction model and parameter combination of UAV hyperspectral images need to be determined to reduce unnecessary waste of time in the preprocessing and provide high-precision data support for the application of UAV hyperspectral images. In this study, the geometric correction accuracy under various geometric correction models (including affine transformation model, local triangulation model, polynomial model, direct linear transformation model, and rational function model) and resampling methods (including nearest neighbor resampling method, bilinear interpolation resampling method, and cubic convolution resampling method) were analyzed. Furthermore, the distribution, number, and accuracy of control points were analyzed based on the control variable method, and precise ground control points (GCPs) were analyzed. The results showed that the average geometric positioning error of UAV hyperspectral images (at 80 m altitude AGL) without geometric correction was as high as 3.4041 m (about 65 pixels). The optimal geometric correction model and parameter combination of the UAV hyperspectral image (at 80 m altitude AGL) used a local triangulation model, adopted a bilinear interpolation resampling method, and selected 12 edge-middle distributed GCPs. The correction accuracy could reach 0.0493 m (less than one pixel). This study provides a reference for the geometric correction of UAV hyperspectral images. Keywords: geometric correction, hyperspectral images, unmanned aerial vehicle (UAV), ground control point (GCP)DOI: 10.25165/j.ijabe.20241703.7103Citation: Tian W Z, Kan Z, Zhao Q Z, Jiang P, Wang X W, Liu H Q. Optimal combination of the correction model and parameters for the precision geometric correction of UAV hyperspectral images. Int J Agric & Biol Eng, 2024; 17(3): 173-184.